Long‐term facilitation of expiratory and sympathetic activities following acute intermittent hypoxia in rats. (3rd March 2016) - Lemes, E. V.; Aiko, S.; Orbem, C. B.; Formentin, C.; Bassi, M.; Colombari, E.; Zoccal, D. B.
Abstract: Aim: Acute intermittent hypoxia (AIH) promotes persistent increases in ventilation and sympathetic activity, referred as long‐term facilitation (LTF). Augmented inspiratory activity is suggested as a major component of respiratory LTF. In this study, we hypothesized that AIH also elicits a sustained increase in expiratory motor activity. We also investigated whether the expiratory LTF contributes to the development of sympathetic LTF after AIH. Methods: Rats were exposed to AIH (10 × 6–7% O2 for 45 s, every 5 min), and the cardiorespiratory parameters were evaluated during 60 min using in vivo and in situ approaches. Results: In unanesthetized conditions ( n = 9), AIH elicited a modest but sustained increase in baseline mean arterial pressure (MAP, 104 ± 2 vs. 111 ± 3 mmHg, P < 0.05) associated with enhanced sympathetic and respiratory‐related variabilities. In the in situ preparations ( n = 9), AIH evoked LTF in phrenic (33 ± 12%), thoracic sympathetic (75 ± 25%) and abdominal nerve activities (69 ± 14%). The sympathetic overactivity after AIH was phase‐locked with the emergence of bursts in abdominal activity during the late‐expiratory phase. In anesthetized vagus‐intact animals, AIH increased baseline MAP (113 ± 3 vs. 122 ± 2 mmHg, P < 0.05) and abdominal muscle activity (535 ± 94%), which were eliminated after pharmacological inhibition of the retrotrapezoid nucleus/parafacial respiratory group (RTN/pFRG). Conclusion: These findings indicate that increased expiratory activity is also an important component of AIH‐elicited respiratory LTF. Moreover, the development of sympathetic LTF after AIH is linked to the emergence of active expiratory pattern and depends on the integrity of the neurones of the RTN/pFRG.